Using ERG inquiry to evoluate otoplasty satisfaction in an otorhinolaryngology medical residency training hospital - Marone, Silvio Antonio Monteiro; Filho, Tarcisio Aguiar Linhares; Ishie, Renato Tadao; Dode, Otavio Borio; Faria, Bernardo Campos; Rodrigues, Jose Luiz Teixeira; de Souza, Marcio Antonio (Elsevier, 2012)
The ear deformity surgery intervention impact on psychological and self-esteem aspects, in adults and children, is well documented. Recently, the studys are focused on patient satisfaction, funcional result and impact on quality of life. Any modification on patient's quality of life has been a challenge. The use of valid and established questionnairies, like Glasgow Benefit Inventory (GBI), assists on data analyse, turning it consistent. Aim: The aim of this study is to evaluate the impact on patients quality of life after otoplasty, through the GBI questionnaire. Methods: Retrospective study including patients underwent otoplasty, within july of 2009 to july of 2010. The data were collected through questionnaire applied by medical resident on 90 post-surgical return. Results: 36 patients answered the questionnaire. There was increase on patients quality of life demonstrated by positive mediana obtained through out questinnaire. There were no significantly differences between age and sex. Conclusion: The patients are satisfied with post-surgical results. There was increase on patients quality of life conform positive results obtained. The use of GBI showed easy and elucidative.
Keywords: Ear auricle; Patient satisfaction; Plastic; Surgery